ҚАДИМГИ ТУРКИЙ ХАЛҚЛАР МИФО-ЭПИК ТАСАВВУРЛАРИДА ҲИМОЯ ТОТЕМЛАРИ ТАВСИФИ - Алимкулов, Э. (SCIENCE and SOCIETY, 2022)
This article analyzes the expression of protective totems in the mytho-epic imaginations of the ancient Turkic peoples. It has been analyzed that different totem animals are associated with certain constellations of stars and planets, resulting in the formation of a unique symbol for each environment. The essence of the article is to determine whether the ancient religious symbols have retained their mysterious nature over the centuries and religions, and have left their mark on the process of movement of huge masses of people over great distances.